CONTEXT IN MEANING CONSTRUCTION: A FUNCTIONAL LINGUISTICS APPLICATION TO LITERARY TEXTS - Nurul Fadhillah; Andi Asrifan; Nurlaila Nurlaila; Alexis Arizabal Enriquez (Linguists : Journal of Linguistics and Language Teaching, 2025)
Context and meaning formation are crucial to functional linguistics, especially literary texts. Using language within texts and meanings drawn from textual units to form interpretations, this essay examines this dynamic. Based on systemic-functional linguistics (SFL), the exploration stresses language's flexibility and ability to connect micro and macro textual elements. The study uses Halliday's context description as a fluid, ever-changing construct to analyse how context influences and reshapes meaning through meaning-making. The structure explains the context, analyses lexicogrammatical selections and patterns, and applies these theoretical descriptions to literary narratives. The study examines fictive narratives, integrates socio-semantic theory to show how context works in diverse literary settings, and reflects on SFL in literary studies. According to functional linguistics, literary interpretation is based on the fundamental processes that shape literary texts. So that understanding related to language constructing meaning in literature by using genre-specific frameworks, digital humanities tools, cross-cultural studies, interdisciplinary collaborations, and dynamic socio-cultural contexts can be better and these methods will illuminate the broad and complex realm of literary expression